Oligodendrocyte Wars - Richardson, William D (Nat Rev Neurosci, 2006)
Oligodendrocyte precursors first arise in a restricted ventral part of the embryonic spinal cord and migrate laterally and dorsally from there. Later, secondary sources develop in the dorsal cord. Normally the ventrally-derived precursors compete with and suppress their dorsal counterparts. There are ventral and dorsal sources in the forebrain too but here the more dorsal precursors prevail and the ventral-most lineage is eliminated during postnatal life. How do the different populations compete and what is outcome of the competition? Do different embryonic origins signify different functional subgroups of oligodendrocytes?